Question

15x-20=6x-(x+2)+(-x+3)

288

likes1438 views

Jayne

4.4

84 Answers

Remove parentheses $(-a)=-a$
$15x-20=6x-(x+2)-x+3$

Group like terms
$15x-20=6x-x-(x+2)+3$

Add similar elements: $ 6x-x=5x$
$15x-20=5x-(x+2)+3$

Expand $5x-(x+2)+3:{\quad}4x+1$
$15x-20=4x+1$

Move $ 20 $ to the right side
$15x=4x+21$

Move $ 4x $ to the left side
$11x=21$

Divide both sides by $11$
$x=\frac{21}{11}$

Frequently asked questions (FAQs)

What is the formula for calculating the sample correlation coefficient?

+

Math question: "What is the vertex form equation of a quadratic function with vertex at (2, -3) and the x-intercepts at (-1, 0) and (5, 0)?"

+

What is the value of sin(30°) + cos(60°) + tan(45°) - csc(90°)?

+

New questions in Mathematics